A study of the relationships among university students’ attitudinal variables and academic achievement in statistics - Ernest Larbi; Francis Ohene Boateng; Mavis Okyere (Journal of Education and Learning (EduLearn), 2026)
This study investigated the relationship among university students’ attitudinal variables and their achievement in statistics. The study also examined the relative contribution that each variable makes to their academic achievement. The study sample comprised 96 university students. Data were collected using a self-designed questionnaire. The reliability coefficients of the various subscales of the piloted questionnaire exceeded 0.70 and were found good to use. The analysis of the data showed a significant positive correlation among three of the students’ attitudinal subscales, namely interest towards statistics and academic achievement (r=0.315, p=0.001), motivation to study the subject and academic achievement (r=0.375, p=0.000) and usefulness of statistics and academic achievement (r=0.268, p=0.004). However, there was a positive low, but insignificant, correlation between anxiety and academic achievement (r=0.218, p=0.084). Further analysis, using multiple regression, showed that all the students’ attitudinal variables, except anxiety, made a significant relative contribution to their academic achievement in statistics. It was recommended that lecturers should help to develop students’ interest and motivation, educate them on the usefulness of statistics, and also, consciously try and reduce university students’ anxiety towards statistics.